Genotypic analysis of Tropheryma whipplei from patients with Whipple disease in the Americas. Issue 10 (6th April 2017) - Rollin, Dominique C; Paddock, Christopher D; Pritt, Bobbi S; Cunningham, Scott A; Denison, Amy M
Abstract : Tropheryma whipplei, the agent of Whipple disease, causes a rare bacterial disease that may be fatal if not treated. The classical form of the disease includes diarrhoea, weight loss, arthritis, endocarditis and neurological manifestations. Genotyping studies done in Europe, Africa and Asia showed high genetic diversity with no correlation between genotypes and clinical features, but contributed to a better understanding of the epidemiology of the disease. More than 70 genotypes have been described. No similar assessment of T. whipplei in the USA and the Caribbean has been performed. In this study, we describe genetic analysis of DNA from histopathological samples obtained from 30 patients from the Americas with Whipple disease and compare the genotypes with those previously identified. Complete genotypes were obtained from 18 patients (60%). Only 4 genotypes were previously described, and 14 were newly reported, confirming the diversity of T. whipplei strains.